Development of IPAS Teaching Materials with the RADEC Model Based on Metacognitive Strategies to Enhance Critical and Creative Thinking Skills of Elementary School Students - Jumanto Jumanto; Udin Syaefudin Sa'Ud; Wahyu Sopandi (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study is to develop IPAS teaching materials using the RADEC model based on metacognitive strategies to enhance critical and creative thinking skills among elementary school students. The research follows the Research & Development approach with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The study involves 84 elementary school students in Surakarta. Data were collected through literature review, expert validation, pretests and posttests, observations, interviews, and documentation. Validation results confirmed that the developed book is valid and suitable for use in terms of content, language, and presentation. A paired sample T-test was conducted on the pretest and posttest results of critical and creative thinking skills for 84 student respondents. The t-test results indicated a significance value of 0.00<0.05 for both pretest and posttest scores of critical thinking skills and creative thinking skills. This suggests a significant difference in the average scores between the pretest and posttest, indicating the influence of the developed book on critical and creative thinking skills. The NGain test results for pretest and posttest scores of critical thinking skills were 70.9252, and for creative thinking skills, it was 70.9284. With these values, it can be concluded that the developed book falls into the category of being sufficiently effective in influencing the critical and creative thinking skills of students